Synthesis, characterization and theoretical studies of nitroxoline azo dye metal complexes and their role in mitigation of rheumatoid arthritis - Hoda A. El-Ghamry; Mohamed Gaber; Mariam S. Napolion; Amira Atta; Tarek M. Mohamed; Nadia A. El‐Wakiel (Scientific Reports)
Abstract In this work, an azo dye ligand of 2,6-dichloroaniline with nitroxoline (CPAQ), and its Zn(II), Cu(II), Cd(II), Ni(II) and Co(II) complexes have been synthesized. The structures of the synthesized compounds have been elucidated applying analytical and spectral tools. According to these results, all complexes proved to have a tetrahedral structure, except Ni(II) complex, which has an octahedral geometry. Analytical results also inferred the formation of Co(II) and Ni(II) complexes in the molar ratio 1M:1L and the remaining complexes in 1M:2L molar ratio. For further insight into the complexes’ geometry, bond lengths, bond angles, and electronic characteristics with respect to the organic ligand were assigned in addition to DFT calculations. HOMO and LOMO calculations show the Co(II) complex is more reactive. The interactions of the target compounds with the Mus musculus ADA enzyme structure (PDB ID: 1a4m) were estimated by applying molecular docking studies. The inhibitory effect of the synthesized compounds on adenosine deaminase enzyme (ADA) activity was tested in-vitro, showing the Co(II) to be the most active.